Majas dalam Lirik Lagu Misramolai Album Tigo Bulan Cinto Tajalin - Fitraneli, Fitraneli; Amir, Amril; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This research is to describe (1) the kind of figures of speech that is used in the song of Misramolai’s Album of Tigo Bulan Cinto Tajalin, (2) the function of the kind of figures of speech in the lyric of song of Misramolai’s Album Tigo bulan cinto tajalin. The data in this research are the figures of speech that is looked from the kind of figure of speech and the function of figures of speech Misramolai’s song’s lyric in the album,  Tigo Bulan Cinto Tajalin. This research is from the lyrics of the 10 songs of misramolai’s in the album Tigo Bulan Cinto Tajalin. The data is collected by: listening, transcript it, clarifying, and marking the word. Base on the research there are 59 figures of speech which function to make it concrete, to make it clear, to make it beautiful, and to make it great.